2022
DOI: 10.29121/granthaalayah.v10.i10.2022.4815
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation and Diversity of Bacteria of the Vibrio and Salmonella Genera Isolated in a Few Underground Water Points Developed in the Commune of Ntui (Mbam-Et-Kim Department, Center-Cameroon)

Abstract: A study aimed at evaluating the seasonal variation of Vibrio and Salmonella in the developed groundwater used for drinking water in the commune of Ntui, Center Region of Cameroon was conducted from January to July 2021. The microorganisms sought were Aerobic Heterotrophic Mesophilic Bacteria (BHAM), bacteria of the Vibrio and Salmonella genera. These bacteria were isolated from ten (10) groundwater points by the surface spreading technique on ordinary agar for BHAMs and that of filter membranes on Thiosulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…This low thermal variation recorded over the study period could be due to the seasons or to the influence of sunshine, as the sun's rays reach the surface of the water directly at certain points. The data obtained during the study are similar to those of Noah Ewoti et al, [8] and Baleng et al [9], who worked on the microbiological and physicochemical quality of some water points in Olézoa and the town of Ntui respectively. In fact, these [6], this could come from detergents, or even faecal pollution that reaches the environment via runoff.…”
Section: Physico-chemical Parameterssupporting
confidence: 85%
See 2 more Smart Citations
“…This low thermal variation recorded over the study period could be due to the seasons or to the influence of sunshine, as the sun's rays reach the surface of the water directly at certain points. The data obtained during the study are similar to those of Noah Ewoti et al, [8] and Baleng et al [9], who worked on the microbiological and physicochemical quality of some water points in Olézoa and the town of Ntui respectively. In fact, these [6], this could come from detergents, or even faecal pollution that reaches the environment via runoff.…”
Section: Physico-chemical Parameterssupporting
confidence: 85%
“…They have shown that these waters harbour a bacterial microflora consisting of pathogenic bacteria such as V. cholerae and V. parahaemolyticus [8]. In addition to vibrioplankton, these waters harbour pathogenic bacteria of the Salmonella genus, such as S. enterica [9]. In addition, the parameters likely to influence the abundance dynamics of these germs are temperature, pH and conductivity [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation